Recent Advances and Future Directions in the Understanding of Mucormycosis - Garre, Victoriano (Frontiers in Cellular and Infection Microbiology, 2022)
Mucormycosis is an emerging infection caused by fungi of the order Mucorales that has recently gained public relevance due to the high incidence among COVID-19 patients in some countries. The reduced knowledge about Mucorales pathogenesis is due, in large part, to the historically low interest for these fungi fostered by their reluctance to be genetically manipulated. The recent introduction of more tractable genetic models together with an increasing number of available whole genome sequences and genomic analyses have improved our understanding of Mucorales biology and mucormycosis in the last ten years. This review summarizes the most significant advances in diagnosis, understanding of the innate and acquired resistance to antifungals, identification of new virulence factors and molecular mechanisms involved in the infection. The increased awareness about the disease and the recent successful genetic manipulation of previous intractable fungal models using CRISPR-Cas9 technology are expected to fuel the characterization of Mucorales pathogenesis, facilitating the development of effective treatments to fight this deadly infection.